PENANGANAN KOMPLAIN TAMU OLEH GUEST RELATION OFFICER DI THE TRANS LUXURY HOTEL BANDUNG - Indrawan, Muhammad Rafli; Mantri, Yaya Mulya (Jurnal Perhotelan dan Pariwisata, 2023)
Guest complaint handling is one of the important aspects in the hospitality industry that directly affects customer satisfaction and loyalty. This research aims to analyze and evaluate the guest complaint handling process by Guest Relation Officers at a five-star hotel in Bandung. The method used in this research is a qualitative approach with data collection through in-depth interviews and direct observation. The results showed that communication skills, empathy and product knowledge are key in resolving guest complaints.